1995
DOI: 10.1007/bf00029320
|View full text |Cite
|
Sign up to set email alerts
|

Roots, nutrients and their relationship to spatial patterns

Abstract: Ecosystem sustainability and resilience after a disturbance may be regulated by processes occurring at smaller spatial scales. The matrix of different spatial environments are created by (1) individual plants that accumulate higher concentrations of specific nutrients, trace elements or defensive plant secondary chemicals and thereby modify the chemistry of their ecological space and/or rates of processes, (2) the presence of structures (e.g., coarse woody debris) that may buffer some micro-environments from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 50 publications
0
17
0
4
Order By: Relevance
“…In fact, Vogt et al [14] noted that decaying logs acted as refuges for mycorrhizal fungi during dry periods or after disturbances. Therefore, it can be expected that decaying logs will contribute to keep the underlying soil moister than the soil that is covered only by the forest floor litter.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Vogt et al [14] noted that decaying logs acted as refuges for mycorrhizal fungi during dry periods or after disturbances. Therefore, it can be expected that decaying logs will contribute to keep the underlying soil moister than the soil that is covered only by the forest floor litter.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have not been designed to sample the spatial heterogeneity that normally exists in a plot, because the questions driving the research required only a site average with preferably a small standard deviation (Vogt et al, 1995). Although this low-resolution research is necessary, it does overlook a rich abundance of information found at a higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Para determinada distância entre raízes, o grau de competição aumenta com o aumento da difusão efetiva, resultando em maior potencial de competição por nitrato do que por K ou por íons relativamente imóveis, como P. O conceito de justaposição das zonas de depleção é menos aplicável para água e nutrientes dissolvidos, como o N, que são primariamente supridos para as raízes por fluxo de massa. Para esses nutrientes, a competição depende tanto da absorção de nutrientes quanto de água (VOGT et al, 1995).…”
Section: As Raízes E a Competição Por áGua E Nutrientesunclassified